Glycine reduces tissue lipid peroxidation in hypoxia-reoxygenation-induced necrotizing enterocolitis in rats - Meyer,Karine Furtado (2006)
PURPOSE: To assess the protective effect of glycine in an experimental model of Neonatal Necrotizing Enterocolitis (NEC). METHODS: Fifty (50) neonatal Wistar rats, from a litter of six female rats and weighing 4 to 6 grams, were used. Five animals were cannibalized and the 45 remaining were distributed into three groups: the G1 normal control group (n=12); the G2 Group (n=16), of animals that underwent hypoxia-reoxygenation (HR); the G3 Group of animals (n=17) that underwent HR following a 5% intraperitoneal glycine infusion. The animals underwent hypoxia in a CO2 chamber receiving an air flow of 100% CO2 for 5 minutes and reoxygenation receiving an O2 flow at 100% for 5 minutes. One centimeter long small bowel and colon segments were prepared for histological analysis. The rest of the bowel was removed in a block and frozen at minus 80°C for homogenization and determination of tissue malondialdehyde (MDA). Tissue lesions were classified as Grade 0 to Grade 5, according to the level of damaged mucosa. RESULTS: The animals in Group G1 had levels of small bowel and colon lesion significantly smaller as compared to the animals in Groups G2 and G3. The G2 group had mean MDA values significantly higher than the animals in the G1 (p = .015) and G3 (p=0.021) groups. MDA values did not differ significantly (p = 0.992) for the animals in groups G1 and G3. CONCLUSION: Glycine reduces tissue MDA levels (a measurement of lipid peroxidation) following HR in neonatal rats.